Regional Determinants of Entrepreneurship in a Small Economy: Panel Data Evidence from Scotland. - Andrew Ross (European Regional Science Association (ERSA), 2011)
This paper analyses the spatial variation of new entrepreneurial activity across 32 Scottish regions for the period 1998-2007. Entrepreneurship is widely recognised as a key determinant of economic growth, regional prosperity and sustainable development. Using data from the Value Added Tax (VAT) register, this paper estimates spatial variation in new entrepreneurial activity using a panel data model. Results show that there is considerable variation in entrepreneurship across Scottish regions and that this variation may be explained by demand and supply factors, policy and cultural factors and agglomeration benefits. Given that Scotland has recently suffered from low levels of entrepreneurship compared with other parts of the UK and similar sized smaller countries, this paper provides relevant and timely findings, as Scotland attempts to recover from the recent recession.
Keywords: 330